(Table 1) Paleocoordinates of deep-sea drilling sites in Neogene - Elena V Ivanova; Alexandra A Ivanova (PANGAEA, 1996)
Reconstruction of climatic zonation and features of surface water circulation in the Indian Ocean for seven selected time intervals is presented based on DSDP/ODP data on distribution of planktonic foraminifera species in Neogene sediments of the Indian Ocean with regard to new palinspastic reference schemes. In Neogene two climatic signs are recognized: at the end of Early Miocene and in Early Pliocene. The equatorial divergence and the monsoon-related Hindustan upwelling presumably existed since Early Miocene, and the Arabian-Somalian upwelling is traced at least since Middle Miocene. In Late Miocene, latitudinal zonation was established over the entire area of the ocean, while in Early-Middle Miocene its northwestern part significantly differed from the northeastern one.
Supplement to: Ivanova, EV; Ivanova, AA (1996): Reconstruction of climatic zonation and features of the surface water circulation in the Indian Ocean in Neogene from planktonic foraminifera. Translated from Okeanologiya, 1996, 36(4), 622-633, Oceanology, 36(4), 586-597